“I have never felt so alone and vulnerable” – A qualitative study of bereaved people’s experiences of end-of-life cancer care during the Covid-19 pandemic - Lara Burton; Silvia Goss; Stephanie Sivell; Lucy E. Selman; Emily Harrop (BMC Palliative Care)
Abstract Background COVID-19 drastically affected healthcare services world-wide. In the UK, many cancer services were overwhelmed as oncology staff were reassigned, and cancer diagnoses and treatments were delayed. The impact of these pressures on end-of-life care for patients with advanced cancer and their relatives is not well understood. Methods Secondary thematic analysis of qualitative survey and interview data, collected from family members and close friends bereaved by cancer, as part of a national COVID-19 bereavement study (Survey N = 156; Interview N = 10). Results Four key themes were identified: The impact of COVID-19 on contact with patients towards the end of life; Mixed experiences of support for family members; Variable communication quality from health and social care professionals; Prioritisation of COVID-19 and its impact on patient care. Hospital care was perceived more negatively than community care in almost all areas, while support from cancer charities and district nurses was appreciated the most. Almost all participants felt that COVID-19 was detrimentally prioritised over care for their relative/friend. Conclusions People bereaved by cancer were uniquely affected by pandemic-restrictions and disruptions to services. As services re-build post-pandemic, improvements in palliative care in hospitals, investment into community care, and ensuring compassionate communication with patients and families must be prioritised, alongside preparedness for future pandemics or similar events.